Social protection systems in vulnerable families: their importance for the public health - Arcos, Estela; Sanchez, Ximena; Toffoletto, Maria Cecilia; Baeza, Margarita; Gazmuri, Patricia; Muñoz, Luz Angélica; Vollrath, Antonia (Revista de Saúde Pública, 2014)
OBJECTIVE To analyze the effectiveness of the Chilean System of Childhood Welfare in transferring benefits to socially vulnerable families. METHODS A cross-sectional study with a sample of 132 families from the Metropolitan Region, Chile, stratified according to degree of social vulnerability, between September 2011 and January 2012. Semi-structured interviews were conducted with mothers of the studied families in public health facilities or their households. The variables studied were family structure, psychosocial risk in the family context and integrated benefits from the welfare system in families that fulfill the necessary requirements for transfer of benefits. Descriptive statistics to measure location and dispersion were calculated. A binary logistic regression, which accounts for the sample size of the study, was carried out. RESULTS The groups were homogenous regarding family size, the presence of biological father in the household, the number of relatives living in the same dwelling, income generation capacity and the rate of dependency and psychosocial risk (p ≥ 0.05). The transfer of benefits was low in all three groups of the sample (≤ 23.0%). The benefit with the best coverage in the system was the Single Family Subsidy, whose transfer was associated with the size of the family, the presence of relatives in the dwelling, the absence of the father in the household, a high rate of dependency and a high income generation capacity (p ≤ 0.10). CONCLUSIONS The effectiveness of benefit transfer was poor, especially in families that were extremely socially vulnerable. Further explanatory studies of benefit transfers to the vulnerable population, of differing intensity and duration, are required in order to reduce health disparities and inequalities.